A case of ovarian torsion in a patient carrier of a FSH receptor gene mutation previously affected by spontaneous ovarian hyperstimulation syndrome. (February 2015) - Di Carlo, C.; Savoia, F.; Fabozzi, A.; Gargano, V.; Nappi, C.
Abstract We here report a case of ovarian torsion in a patient with an history of two previous episodes of spontaneous ovarian hyperstimulation syndrome during her two pregnancies. A mutation of follicle-stimulating hormone receptor (FSHr) gene was identified in this patient and in other members of the family. Two years after her successful second pregnancy, the patient showed signs of severe thyroiditis during administration of oral contraceptive, with suppressed TSH and increased thyreoglobulin, in the absence of any abnormalities of the auto-antibodies. In few days, she developed severe pelvic pain and ultrasonographic evidence of increased ovarian volume. She underwent laparoscopy with unilateral adnexectomy for ovarian ischemic necrosis due to adnexal torsion. Our experience suggests that patients' carrier of a mutation of FSHr gene are at risk of ovarian pathologies also when non-pregnant and in the presence of low TSH levels. Further investigations are needed for an appropriate knowledge of typical and atypical manifestations of spontaneous ovarian hyperstimulation syndrome.